Study on a New Catalyst Tungsten Phosphide for the Carbon Dioxide Reforming of Methane and Its Preparation Conditions - Yang, Chunyan; Li, Xiancai; Yang, Yifeng; Yang, Xiaomao; Yang, Aijun (Asian Journal of Chemistry, 2013)
A new tungsten phosphide was successfully synthesized for the carbon dioxide reforming of methane (CH4-CO2 reforming). The catalysts were prepared by combining citric acid and temperature programmed reduction of phosphotungstate precursor, which was characterized by X-ray diffraction. This paper focuses on investigating that the influence of preparations on activity of tungsten phosphide for CH4-CO2 reforming. The activity results indicate that the activity and stability of catalyst was prepared under the proper conditions. On this basis, a new easier preparation was proposed, which was prepared by associating calcining with reduction H3O40PW12·XH2O and (NH4)2HPO4, the prepared catalyst showed a little bit worse of the activity. The activity test results of tungsten phosphide for CH4-CO2 reforming show that it produce synthesis gas with lower H2 to CO ratio than the conventional catalysis for the CH4-CO2 reforming.